2017
DOI: 10.1080/10548408.2017.1320262
|View full text |Cite|
|
Sign up to set email alerts
|

How are food value video clips effective in promoting food tourism? Generation Y versus non–Generation Y

Abstract: The purpose of this study was to identify the effects of a food tourism video clip created by a destination marketing organization (DMO) on potential tourists' perceptions of the destination's food values, familiarity with the destination's food, behavioral involvement with the destination's food, and intention to visit the destination for food tourism. A number of important findings were generated. First, of the five food values, "global food" and "attractive food" significantly influenced the respondents' fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 71 publications
3
58
0
7
Order By: Relevance
“…These four domains are consistent with those proposed in previous literature. For example, the importance of food quality is widely supported by previous studies (Horng et al, ; Jiménez‐Beltrán et al, ; Kim et al, ; Kim & Evans, 2012; Tsai, ). The significance of food uniqueness is also confirmed by the findings of previous studies (Goolaup & Mossberg, ; Guan, ; Kauppinen‐Räisänen et al, ).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…These four domains are consistent with those proposed in previous literature. For example, the importance of food quality is widely supported by previous studies (Horng et al, ; Jiménez‐Beltrán et al, ; Kim et al, ; Kim & Evans, 2012; Tsai, ). The significance of food uniqueness is also confirmed by the findings of previous studies (Goolaup & Mossberg, ; Guan, ; Kauppinen‐Räisänen et al, ).…”
Section: Discussionmentioning
confidence: 79%
“…A review of local food tourism literature suggests that local food attributes can be summarized as falling into the categories of food quality, tradition, uniqueness, and service quality (Chi, Chua, Othman, & Karim, ; Kim & Choe, ; Kim & Eves, ; Verbeke & Poquiviqui López, ). Previous studies have consistently shown that positive perceptions of the quality of local food positively effects future intentions (Adongo, Anuga, & Dayour, ; Chi et al, ; Horng, Liu, Chou, & Tsai, ; Jiménez‐Beltrán, López‐Guzmán, & González Santa Cruz, ; Kim, Choe, & Lee, ; Kim & Eves, ; Mynttinen, Logrén, Särkkä‐Tirkkonen, & Rautiainen, ; Stone et al, ). A study by Kim and Eves () found that the sensory appeal of local food is a significant factor leading to its consumption in tourist destinations.…”
Section: Local Food Gastronomy and Its Effects On Intentions For Recomentioning
confidence: 97%
“…However, only a few papers have underlined the need to split the image formation process into at least three different stages (before/a priori, during/in situ, and after/a posteriori), as image is a dynamic concept, and peoples' perceptions can change over time (Gallarza et al, ; Gunn, ; Kim, Mckercher, & Lee, ; Smith et al, ). Extraneous factors or reasons can often influence a change of image perception such as watching advertising campaigns (Pan, Santos, & Kim, ; Shani, Chen, Wang, & Hua, ) or TV series/films (Kim, Kim, Agrusa, & Lee, ; Shani, Wang, Hudson, & Gil, ; Terzidou, Stylidis, & Terzidis, ), engaging with social media (Kim, Choe, & Lee, ; Pike et al, ), and attending or watching internationally significant (Gartner & Shen, ) or mega events (Kim & Morrison, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Local food is presented in suitable ways by restaurants so that tourists can accept local food. Accordingly, food tourists are supposed to use three types of quality attributes to judge their gastronomic experience [21,22]: Functional-food quality; humanic-service quality; and mechanical-the physical environment [23][24][25][26][27][28][29][30]. Moreover, traditional cooking needs to connect with modern consumers; therefore, quality attributes should be considered to make tourists satisfied and loyal [22].…”
Section: Introductionmentioning
confidence: 99%